2017
DOI: 10.1016/j.bbr.2016.11.044
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine treatment reverses depressive-like behavior and reduces DNA methyltransferase activity induced by maternal deprivation

Abstract: Stress in early life has been appointed as an important phenomenon in the onset of depression and poor response to treatment with classical antidepressants. Furthermore, childhood trauma triggers epigenetic changes, which are associated with the pathophysiology of major depressive disorder (MDD). Treatment with atypical antipsychotics such as quetiapine, exerts therapeutic effect for MDD patients and induces epigenetic changes. This study aimed to analyze the effect of chronic treatment with quetiapine (20mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 67 publications
(86 reference statements)
3
29
0
2
Order By: Relevance
“…MS promotes change in the expression of DNMT1 and DNMT3a, which are representative of maintenance and de novo methyltransferase activity, respectively. Our findings are consistent with a previous study showing that MS (3 h daily from PND 1 to PND 10) increased DNMT activity in the hippocampus of adult rats . Another study found an increase in DNMT1 expression in the dentate gyrus‐derived neural precursor cells of adult rats subjected to MS (3 h daily from PND 2 to PND 14) .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…MS promotes change in the expression of DNMT1 and DNMT3a, which are representative of maintenance and de novo methyltransferase activity, respectively. Our findings are consistent with a previous study showing that MS (3 h daily from PND 1 to PND 10) increased DNMT activity in the hippocampus of adult rats . Another study found an increase in DNMT1 expression in the dentate gyrus‐derived neural precursor cells of adult rats subjected to MS (3 h daily from PND 2 to PND 14) .…”
Section: Discussionsupporting
confidence: 93%
“…ESC reversed hypermethylation of the p11 gene promoter in the prefrontal cortex of a genetic rat model of depression and reduced mRNA expression of DNMT1 and DNMT3a . A more recent study found that the antipsychotic drug, quetiapine, reversed depression‐like behavior and increased maternal deprivation‐induced DNMT activity in the hippocampus . We found that chronic ESC treatment clearly prevented the MS‐induced decreases in DNMT1 and DNMT3a expression in the adult hippocampus.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations